Resonance Raman detection of a ferrous five-coordinate nitrosylheme b 3 complex in cytochrome cbb 3 oxidase from Pseudomonas stutzeri - Pinakoulaki, Eftychia; Stavrakis, Stavros; Varotsis, Constantinos (My University, 2002)
Understanding the chemical nature of the nitric oxide (NO) moiety of nitrosylheme copper oxidases is crucial for elucidation of the NO activation process. In the present work, direct resonance Raman spectroscopic observation of both the Fe 2+-NO and the N-O stretching modes unambiguously establishes the vibrational characteristics of the NO-bound heme moiety in cytochrome cbb 3 from Pseudomonas stutzeri. Addition of NO to fully reduced enzyme causes the rupture of the proximal His-heme b3 bond resulting in the formation of a five-coordinate heme b 3 2+-NO species with ν(Fe-NO) and ν(NO) at 524 and 1679 cm -1, respectively. The frequencies of the nitrosyl species we detect are very similar to those obtained in other model- and protein heme-NO complexes. To account for this observation, we propose a model describing the oxidation and ligand-binding states in fully reduced cytochrome cbb 3 upon addition of NO
Keywords: Raman spectrometry; Copper; Heme; Cytochrome oxidase; Nitric oxide; Chemical structure; Hydrogen bonding; Pseudomonas